Beyond the firm : (Oxford University Press, 1997)
Special attention has been devoted in recent years to the distinctive features of Japanese economic organization, and in particular the ways in which firms in Japan have created alternatives to arm's length markets or vertically integrated hierarchies. This book brings together contributions from international scholars presenting analysis and evidence of these phenomenon. How have these business alliances evolved? Are they a particularly Japanese or Asian phenomenon? Are there historical comparisons in Europe and America? What distinguishes 'corporate complexes', 'corporate groups' and 'assembler supplier relationships'? In so doing the book both provides valuable historical detail, raises questions for conventional theories of the firm, offers insight into the resilient international competitiveness of Japanese companies and into the varying institutional characteristics of different business systems and cultures.